2009
DOI: 10.1002/hbm.20861
|View full text |Cite
|
Sign up to set email alerts
|

ERP generator anomalies in presymptomatic carriers of the Alzheimer's disease E280A PS‐1 mutation

Abstract: Although subtle anatomical anomalies long precede the onset of clinical symptoms in Alzheimer's disease, their impact on the reorganization of brain networks underlying cognitive functions has not been fully explored. A unique window into this reorganization is provided by presymptomatic cases of familial Alzheimer's disease (FAD). Here we studied neural circuitry related to semantic processing in presymptomatic FAD cases by estimating the intracranial sources of the N400 event-related potential (ERP). ERPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 102 publications
2
41
0
Order By: Relevance
“…Ochoa et al [8] have found increases in effective connectivity, assessed using information theoretic measures, in the same PreC group during encoding of scene information. This same Colombian kindred has been studied [9] with high-density EEG while performing a picture matching task, in which a first picture provided context and a second picture either matched or did not match that context. This paradigm elicited a characteristic change in the EEG signal-between matching and non-matching trials-400 ms after the presentation of the second picture, the so-called "N400".…”
Section: W Penny Et Al / Dynamic Causal Modeling Of Preclinical Eegmentioning
confidence: 99%
See 4 more Smart Citations
“…Ochoa et al [8] have found increases in effective connectivity, assessed using information theoretic measures, in the same PreC group during encoding of scene information. This same Colombian kindred has been studied [9] with high-density EEG while performing a picture matching task, in which a first picture provided context and a second picture either matched or did not match that context. This paradigm elicited a characteristic change in the EEG signal-between matching and non-matching trials-400 ms after the presentation of the second picture, the so-called "N400".…”
Section: W Penny Et Al / Dynamic Causal Modeling Of Preclinical Eegmentioning
confidence: 99%
“…They found smaller N400 s in right inferotemporal cortex and increased N400 s in left hippocampus and parahippocampus. This paper uses dynamic causal modeling (DCM) [10] to identify the changes in brain connectivity that cause the ERP effects observed in the Bobes et al [9] study. One of the motivations for revisiting this data is that it was acquired in 1999 and since then, follow-up cognitive assessments have periodically been made of subjects with the PSEN1 mutation.…”
Section: W Penny Et Al / Dynamic Causal Modeling Of Preclinical Eegmentioning
confidence: 99%
See 3 more Smart Citations